Penta-O-Galloyl-β-D-Glucose in Pistacia integerrima Targets AMPK-ULK1 and ERK/STAT3 Signaling Axes to Induce ROS-Independent Autophagic Cell Death in Human Lung Cancer Cells - Balkrishna, Acharya; Mulay, Vallabh Prakash; Verma, Sudeep; Srivastava, Jyotish; Lochab, Savita; Varshney, Anurag (Frontiers in Pharmacology, 2022)
Graphical Abstract